2011
DOI: 10.1007/s11033-011-0844-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of p53 and p73 genes polymorphisms in susceptibility to esophageal cancer: a case control study in a northern Indian population

Abstract: Genetic variants in p53 and in its homologue p73 may modulate Esophageal Cancer (EC) risk because they are supposed to influence cell cycle progression, apoptosis and DNA repair. Therefore, we aimed to evaluate the association of p53 intron3 16 bp duplication and p73 G4C14-to-A4T14 polymorphisms with susceptibility to EC in a northern Indian population in 255 EC patients and 255 age and sex matched healthy controls. We found that p53 intron3 16 bp duplication polymorphism was not associated with EC and its cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…In the present study, no association of PIN3 polymorphism with EC risk was observed. This was consistent with a study conducted in other states of North India which revealed no association of PIN3 polymorphism with EC risk (Umar et al, 2012). However, A2A2 genotype of PIN3 polymorphism has been reported to be associated with increased risk of esophageal cancer in Kashmiri North Indian (Malik et al, 2011) and South African (Vos et al, 2003) patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, no association of PIN3 polymorphism with EC risk was observed. This was consistent with a study conducted in other states of North India which revealed no association of PIN3 polymorphism with EC risk (Umar et al, 2012). However, A2A2 genotype of PIN3 polymorphism has been reported to be associated with increased risk of esophageal cancer in Kashmiri North Indian (Malik et al, 2011) and South African (Vos et al, 2003) patients.…”
Section: Discussionsupporting
confidence: 91%
“…To date, there are three reports examining the association between PIN3 ins16bp polymorphism and the risk for EC. Two of these reports found a positive association between A2A2 genotype and EC (Vos et al, 2003;Malik et al, 2011), whereas one study from North India failed to find an association (Umar et al, 2012).…”
Section: Introductionmentioning
confidence: 94%
“…It is known that functional polymorphisms can impact tumor biology and have been implicated in the development and prognosis of several cancers, being highlighted as a potential candidate of the susceptibility for cancer development [8589]. These genetics variants in TP53 may modulate cancer risk because they are also supposed to influence cell cycle progression, apoptosis, and DNA repair [90]. …”
Section: Tp53 Polymorphisms and Risk Of Esophageal And Gastric Cancermentioning
confidence: 99%
“…The combination of nedaplatin and cisplatin at low concentrations were more effective for inhibition of proliferation and the induction of apoptosis in the Eca-109 and the expressions of bcl-2 mRNA and protein were decreased (Su et al, 2012). Our result showed that ECRG2 protein at a high concentration could significantly down-regulate the expressions of bcl-2 mRNA and protein with compared with control group, When ECRG2 was combined with DDP, the bcl-2 mRNA and protein expressions were significantly decreased compared with that when ECRG2 protein was used alone As a key transcription factor, p53 containing 393 amino acids is closely associated with the regulation of cell cycle, the repair of DNA damage, cell apoptosis and tumor suppression Mai et al, 2012;Umar et al, 2012;Vousden et al, 2009). As a tumor suppressor gene, p53 is the most widely mutated gene in human carcinogenesis, which plays an important role in the initiation and development of the tumor (Liu et al, 2010;Zhao et al, 2010).…”
Section: Discussionmentioning
confidence: 99%